Zinc supplementation and immune factors in adults: a systematic review and meta-analysis of randomized clinical trials. Issue 11 (17th June 2022) - Jafari, Alireza; Noormohammadi, Zeinab; Askari, Mohammadreza; Daneshzad, Elnaz
Abstract: Purpose: This systematic review and meta-analysis aimed to investigate the effect of zinc supplementation on immune factors in randomized controlled trials. Methods: A comprehensive search was done in PubMed, Scopus, Web of Science, Embase, and Cochrane databases up to December 2020. We used standard and weighted mean differences and 95% confidence intervals for net changes in selected parameters of immune responses. Subgroup analysis was used to find heterogeneity. Result: Overall, 35 RCTs comprising 1995 participants were eligible for this meta-analysis. There was a significant reduction of circulating CRP (WMD: −32.4; 95% CI: −44.45 to −19.62, p < 0.001), hs-CRP (WMD: −0.95; 95% CI: −1.01 to −0.89, p < 0.001), Neutrophil levels (SMD: −0.46; 95% CI: −0.90 to −0.01, p = 0.043), following zinc supplementation. CD4 level also increased significantly, (WMD: 1.79; 95% CI: 0.57 to 3, p = 0.004). Zinc supplementation had no significant effect on WBC (SMD: −0.66; 95% CI: −1.67 to 0.36, p = 0.204), lymphocyte (WMD: 1.86; 95% CI: −0.86 to 4.58, p = 0.181), monocyte levels (SMD: −0.16; 95% CI: −0.07 to 0.39, p = 0.167), CD3 (SMD: 0.37; 95% CI: −0.49 to 1.22, p = 0.399). Conclusion: Zinc supplementation decreased the CRP, hs-CRP and TNF-α, IL-6, neutrophil and increased CD3 and CD4 level significantly.